Organ-Specific Activation of the Gastric Branch of the Efferent Vagus Nerve by Ghrelin in Urethane-Anesthetized Rats - Hiromi Habara; Yujiro Hayashi; Norio Inomata; Akira Niijima; Kenji Kangawa (Elsevier, 2014)
Abstract.: Ghrelin plays multiple physiological roles such as growth hormone secretion and exerting orexigenic actions; however, its physiological roles in the electrical activity of autonomic nerves remain unclear. Here, we investigated the effects of human ghrelin on several autonomic nerve activities in urethane-anesthetized rats using an electrophysiological method. Intravenous injection of ghrelin at 3 μg/kg significantly and transiently potentiated the efferent activity of the gastric vagus nerve; however, it did not affect the efferent activity of the hepatic vagus nerve. The activated response to ghrelin in the gastric efferent vagus nerve was not affected by the gastric afferent vagotomy, suggesting that this effect was not induced via the gastric afferent vagus nerve. Ghrelin did not affect the efferent activity of the brown adipose tissue, adrenal gland sympathetic nerve, and the renal sympathetic nerve. In addition, rectal temperature and the plasma concentrations of norepinephrine, corticosterone, and renin were also not changed by ghrelin. These findings demonstrate that ghrelin stimulates the gastric efferent vagus nerve in an organ-specific manner without affecting the gastric afferent vagus nerve and that ghrelin does not acutely affect the efferent basal activity of the sympathetic nerve in rats. Keywords:: ghrelin, vagus nerve, sympathetic nerve, gastric, vagotomy